Environmental control as a means of preventing nosocomial infections in the intensive care unit – selected issues - Gniadek, Zofia; Bakuła, Jakub E.; Czapska, Weronika (Nursing Problems / Problemy Pielęgniarstwa, 2025)
An intensive care unit is a place where infections are most common in the hospital, and they mainly include respiratory system issues such as pneumonia associated with mechanical ventilation, vascular access infections, and urinary tract infections associated with the presence of catheters. The pathogens that are most frequently responsible for these infections are gram-negative bacilli ( Klebsiella pneumoniae, Acinetobacter baumannii, Pseudomonas aeruginosa ), which, by developing resistance mechanisms to the antibiotics used, become difficult to treat and are, therefore, the cause of patients’ deaths, or when transmitted to other patients, contribute to spreading infections in the environment. Consequently, when it comes to the treatment and care provided to patients, adherence to clearly defined procedures and standards, which are numerous but extremely important, is becoming vital in protect-ing patients from infections.